Application of Contextual Teaching and Learning Models in Improving the Manasic Understanding of Haji for X-Class Students - Hamka, Hamka; Saleh, Muhammad; K., Abd. Halim (Al-Iftah: Journal of Islamic studies and society, 2021)
This study discusses the application of the Contextual Teaching and Learning (CTL) learning model in improving the understanding of the Hajj rituals of class X students of SMK Amsir 1 Parepare . The research in this thesis aims to determine the increase in students' understanding of the X grade Islamic Religious Education subject at SMK Amsir 1 Parepare by applying the CTL learning model. This type of research is experimental research . The design used was Quasy Experimental Design , the research instrument was a written test. Data collection techniques are test techniques, and documentation; Data management and analysis techniques include Validity Test Statistics, Reliability Testing, and Hypothesis Testing. The results of this study are (1) The increased understanding of students' Hajj rituals in the experimental class after being treated, the post-test results increased was 85.60 while the pre-test results in the experimental class were 67.65 (2) the application of the CTL learning model proved effective in improving students' understanding of the Hajj rituals. This is evidenced by the results of the post-test test in the control class and experimental class, it is obtained t count (9.331) ≥ t table (1.725) (t count is greater than t table) then H 0 is rejected and H 1 is accepted.